A Comparison of Business Improvement Methodologies: Are They Converging Towards One Universal Approach? - Curtis, Richard (2006)
The latter part of the 20th Century saw a significant rise in the popularity of business improvement programmes, driven by the changing competitive environment and the need to continually improve performance in aspects such as cost, quality, customer service, flexibility and pace. Over the last few decades methodologies such as Total Quality Management, Six Sigma, Business Process Re-engineering, Lean and the Theory of Constraints have been used by many organisations to deliver performance improvement.